Scope of Homoeopathic medicines in Internet Gaming Disorder (IGD) (Advancements in Homeopathic Research, 2022)
Backgroud: Internet gaming disorder is a pattern of excessive and prolonged Internet gaming that results in a cluster of cognitive and behavioural symptoms.Objective: To find out the group of homoeopathic drugs that may be indicated in Internet Gaming Disorder (IGD).Methods: Reviewing the Homeopathic literature, Reviewing the studies done on IGD, Finding the group of medicines indicated in IGDResults: Polychrest Homeopathic medicines Stramonium, Belladonna, Nux vomica, Vertrum album, Pulsatilla, Ignatia, Calcarea carbonicum, Platinum, Aurum metallicum, Natrum muriaticum and Lycopodium were selectedConclusion: This study is a step towards profiling of Homoeopathic medicines for IGD. Further studies for clinical verification of these medicines on IGD can be undertaken.
Keywords: Homoeopathy; Internet Gaming Disorder; IGD